PENGARUH LATIHAN BET BERAT TERHADAP KEKUATAN OTOT LENGAN SISWA PEMBINAAN TENIS MEJA PUTRA SMA NEGERI OLAHRAGA PROVINSI RIAU - Zulheri, Deki; Zainur, Zainur; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on the results of observations that the researchers had conducted at the Riau Province High School Sports High School, the students of the table tennis coaching of the Men of High School Sports in the Riau Province were still lacking in arm muscle strength. This is clearly seen during practice and competition. Where coaching students do matches with balanced opponents and play by looking for 3 wins, students are less than optimal in making blows so that when making blows, the ball always does not make it over the net, often even out of the field and athletes tend to lose. Thus, the purpose of this study is whether there is an Effect of Heavy Bet Training on Arm Muscles Strength of Men's Table Tennis Guidance for High School Men of Sports in Riau Province. This research was conducted at the Sports High School of Riau Province, Yossudarso Road No. 103, from April to September 2019. The population in this study were 6 students of men's table tennis coaching at the Sports High School of Riau Province and the entire population was sampled as a total sampling). Based on the analysis carried out, the value of Thitung between the initial test and the final test of heavy beta exercise on arm muscle strength with a Ttable at a significant level of 0.05 indicates a Tcount of 10.3> Ttable of 2.015. So that Ho is rejected and Ha is accepted and from the analysis it can also be concluded that there is an effect of heavy bet training on the arm muscle strength of the men's table tennis coaching students at SMAN Sports in Riau Province.Key Words: Heavy Bet Exercise, Arm Muscle Strength